2006
DOI: 10.1063/1.2422912
|View full text |Cite
|
Sign up to set email alerts
|

Nanopores in carbon nitride nanotubes: Reversible hydrogen storage sites

Abstract: Experimental and theoretical approaches are used to determine hydrogen storage mechanisms in nanopores of multiwalled carbon nitride nanotubes ͑MWCNNTs͒. First, the authors produce ϳ0.6 nm pores on the stems of MWCNNTs by plasma-enhanced chemical vapor deposition. Next, thermal desorption spectra were measured and obtained two different peaks. This is explained by hydrogen desorption barriers of 0.36-0.50 eV attributed to two different types of ϳ0.6 nm pores. Moreover, H 2 adsorption between complete interlaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Despite the fact that there are as yet no experimental reports on the last four 2D phases, the present result of 2D Ge facilitates the study of the trend of property variation among the three group IV elementary 2D phases. Besides, carbon nitride, 26) silicon nitride, 27) and silicon carbide are among the popular artificial materials for synthesis investigation nowadays. Success in fabrication of nanotubes or nanorods of CN 26) and SiN 27) has been reported experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that there are as yet no experimental reports on the last four 2D phases, the present result of 2D Ge facilitates the study of the trend of property variation among the three group IV elementary 2D phases. Besides, carbon nitride, 26) silicon nitride, 27) and silicon carbide are among the popular artificial materials for synthesis investigation nowadays. Success in fabrication of nanotubes or nanorods of CN 26) and SiN 27) has been reported experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, carbon nitride, 26) silicon nitride, 27) and silicon carbide are among the popular artificial materials for synthesis investigation nowadays. Success in fabrication of nanotubes or nanorods of CN 26) and SiN 27) has been reported experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…N1, N2 and N3 indicate pyridine-like nitrogen, graphite-like nitrogen, and gaseous nitrogen molecules encapsulated in the core tube, respectively. 8 These nitrogen configurations act as defect sites, which bind the Co NPs on the CNNTs.…”
Section: Synthesis and Structural Analysis Of Size-controlled Co Nano...mentioning
confidence: 99%
“…[5][6][7] Our previous studies demonstrated that carbon nitride nanotubes (CNNTs) including heterogeneous nitrogen in the carbon network would also be a promising host structure to provide the sites for anchoring metal NPs. 8,9 CNNTs have the great advantage of not needing an additional functionalization process, damaging the pristine structure of the CNNTs unlike the oxidative treatment of CNTs. In addition, the binding energy of metal atoms with CNNTs is larger than that for the pristine structure of CNTs, so they contribute to distribute the metal NPs more uniformly.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated carbon films are frequently classified into four classes: polymer-like films with the highest hydrogen content of up to 50% and up to 60% of hydrogen-terminated sp 3 bonds, diamond-like films with an intermediate H content (about 30%) and a large fraction of C–C sp 3 bonds, hydrogenated tetrahedral carbon films (ta-C:H) with a typically hydrogen content of 25% and the highest sp 3 content of about 70%, and graphite-like films with low hydrogen (<20%) but large sp 2 contents [ 6 ]. Due to these properties, hydrogenated carbon films can be used for super-hard materials [ 1 ], biomaterials [ 7 ], wear-resistant coatings [ 8 ], optical coatings [ 9 ], field enhanced conductors [ 10 ], smart polymer and biopolymer films [ 11 , 12 ], and hydrogen storage devices [ 13 ]. Film characteristics can be suitably tailored for particular applications employing different deposition techniques and precursor gas mixtures, e.g., chemical vapor deposition (CVD) [ 14 ], sputtering [ 15 ], plasma enhanced chemical vapor deposition (PECVD) [ 16 ], and pulsed laser deposition (PLD) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%